A geoecologia das paisagens como subsídio ao planejamento turístico em unidades de conservação - Oliveira, Wellington Romão (2015)
With the creation of protected areas it is necessary to analyze how has given the tourism planning at municipal level. The study area defined by the research was the municipality of Tutóia, located in the northern portion of the state of Maranhão, in the micro Maranhenses Sheets, at 2º 45’ 44” S e longitude 42º 16’ 28” W, having an area of 1,651 , 656 km², making border with the municipalities of Araioses, Paulino Neves, Água Doce do Maranhão, São Bernardo and Santana do Maranhão; It is far from the city of São. luís about 400 km. The municipality consists of two districts: Tutóia and Barro Duro. The overall objective is to use the Geoecology of landscapes as a subsidy to environmental and tourism planning at the municipal level, with the study area the municipality of Tutóia - MA. From the methodological stages of Geoecology landscape, literature searches were conducted from the built-in diagnostics, in order to generate subsidies for action and management plan proposals in the municipality, focused on environmental and tourism planning. Knowing the local reality, and appropriate to the activities in the area is possible to reduce impacts and improve the quality of life of the population in general, with the search for more sustainable activities. The rural ecology and compartmentalized units were identified in order to analyze in more detail the ways of use and the environmental problems identified in each. The tourism potential in the area gives grants for studies aiming at the proper planning and management at the local reality. Attractive already explored have been mapped and analyzed individually. From the detailed knowledge of the area, the local reality and the laws governing the municipality to draw up proposals consistent with reality is possible, seeking to provide subsidies for Tutóia become a more sustainable city, making compatible economic growth, especially from tourism with protection of natural resources.